1995
DOI: 10.1037/0022-006x.63.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Help negation after acute suicidal crisis.

Abstract: This study represents one of the first efforts to empirically differentiate between suicidal patients who complete treatment and those who voluntarily withdraw after resolution of the immediate crisis and, accordingly, before formally beginning treatment or within the first 2 days. Participants were contrasted across a range of variables, including suicide ideation, depression, hopelessness, problem solving, life stress, diagnoses in accordance with the Diagnostic and Statistical Manual of Mental Disorders (3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 12 publications
7
77
1
1
Order By: Relevance
“…It is also accepted that seeking appropriate help offers protection against the development of acute forms of suicidality and completion (Kalafat, 1997). However, there is evidence indicating that acutely suicidal individuals negate, refuse, or avoid help (Barnes, Ikeda, & Kresnow, 2001;Clark & Fawcett, 1992;Rudd, Joiner, & Rajab, 1995). Moreover, there is growing evidence that nonacutely suicidal (subclinical) individuals may also negate help for suicidal thoughts (Carlton & Deane, 2000;Deane, Skogstad & Williams, 1999;Saunders, Resnick, Hoberman & Blum, 1994) and that this trend may not be limited to avoiding help from mental health professionals (Deane, Wilson, & Ciarrochi, 2001).…”
mentioning
confidence: 94%
“…It is also accepted that seeking appropriate help offers protection against the development of acute forms of suicidality and completion (Kalafat, 1997). However, there is evidence indicating that acutely suicidal individuals negate, refuse, or avoid help (Barnes, Ikeda, & Kresnow, 2001;Clark & Fawcett, 1992;Rudd, Joiner, & Rajab, 1995). Moreover, there is growing evidence that nonacutely suicidal (subclinical) individuals may also negate help for suicidal thoughts (Carlton & Deane, 2000;Deane, Skogstad & Williams, 1999;Saunders, Resnick, Hoberman & Blum, 1994) and that this trend may not be limited to avoiding help from mental health professionals (Deane, Wilson, & Ciarrochi, 2001).…”
mentioning
confidence: 94%
“…It is possible that people who were experiencing such high levels of suicidality had either never sought professional help or had discontinued treatment. Not accepting or accessing available helping resources might have been due to the affected person's doubt about the efficacy of treatment (Rudd et al 1995), maladaptive coping strategies of suicidal people (Gould et al 2004;Rudd et al 1995), negative attitudes towards or beliefs about seeking professional help (Carlton and Deane 2000;Wilson) or stigma associated with suicidality (Sudak et al 2008). Low utilization of professional health services among suicidal people has also been described in earlier studies (Borges et al 2010;Husky et al 2012;Johnston et al 2009;Pirkis et al 2003;Wu et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Hence, it can be assumed that some suicides and suicide attempts might be prevented by timely and continuing therapeutic interventions (Mann et al 2005). However, several studies have shown help-negation among suicidal people, that is a "refusal to accept or access available helping resources" (p. 499; Rudd et al 1995). Cognitively, this help-negation was expressed by an inverse relationship between self-reported levels of suicidal ideation or mental health problems and intentions to seek formal help (Carlton and Deane 2000;Deane et al 2001;Wilson et al 2005;Yakunina et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research of individuals presenting after a suicidal crisis has demonstrated that these people reject help because they perceive that no one will be able to help them (Rudd, Joiner & Rajab, 1995). Typically, men who die by suicide are characterized by a lack of openness that may prevent them from voicing their distress or suicidal ideation to professionals (Duberstein, 2001).…”
Section: Discussionmentioning
confidence: 99%